Bioactive Phenolic Compounds from Natural Zygophyllum fabago Plant: Isolation, Purification and Characterization - Omar T. Ali (Journal of Global Pharma Technology, 2016)
This study is to investigate the chemical constituents of the aerial parts of Zygophyllum fabago in Iraq. The compounds were isolated by silica gel and column chromatography from deferent extracts. Their structures were characterized by various spectroscopic data (HPLC, 1H and 13C-NMR) and compared with the literature. As a result, three phenolic compounds were isolated, and their structures were identified as Catechol, Coumarin and Resorcinol. Biological testing of the extracts against six different Gram-positive and Gram-negative bacteria showed significant results.   Keywords: Zygophyllum fabago, Bioactive, Purification.